2020
DOI: 10.1002/mc.23240
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective autophagy induction by withaferin A in prostate cancer cells involves GABARAPL1

Abstract: Withaferin A (WA) is a naturally occurring steroidal lactone with proven cancer chemopreventive activity in preclinical models of different cancers including prostate adenocarcinoma. Previously we compared the RNA‐seq data from control and WA‐treated 22Rv1 human prostate cancer cells to identify mechanistic targets of this phytochemical. The Gene Ontology pathway analysis of the RNA‐seq data revealed significant upregulation of genes associated with autophagy upon WA treatment in 22Rv1 cells. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Total RNA was extracted from FoxQ1 overexpressing SUM159 and MCF‐7 cells and corresponding EV cells ( n = 3 for each) using the RNeasy® Mini kit (Qiagen) following the instructions provided by the manufacturer. Other details of the PCR array were essentially the same as described previously 21 . The data was analyzed using the web‐based software provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from FoxQ1 overexpressing SUM159 and MCF‐7 cells and corresponding EV cells ( n = 3 for each) using the RNeasy® Mini kit (Qiagen) following the instructions provided by the manufacturer. Other details of the PCR array were essentially the same as described previously 21 . The data was analyzed using the web‐based software provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Other details of the PCR array were essentially the same as described previously. 21 The data was analyzed using the web-based software provided by the manufacturer. The threshold cycles were calculated and the genes with values above 35 were considered undetected.…”
Section: Human Autophagy Rt 2 Profiler™ Polymerase Chain Reaction (Pc...mentioning
confidence: 99%
“…Hitherto, several withanolides, including withaferin A, 3‐azido withaferin A, physapubescin B, physapubenolide, and physagulide P, were found to exhibit active cytostatic autophagy (Ma et al, 2017; Rah et al, 2015; Xu et al, 2017; Yu et al, 2017), whereas our group previously found that the cytoprotective autophagy was initiated by physalin A (He, Zang, Feng, Wang, et al, 2013). Intriguingly, withaferin A is quite distinctive since the autophagy induced by withaferin A was cytoprotective in prostate cancer cells(Hahm & Singh, 2020), and in breast cancer cells (Muniraj et al, 2019).…”
Section: Anticancer Mechanisms Of Withanolidesmentioning
confidence: 99%
“…Inhibition of AKT signaling. [ 48–58 ] Renal carcinoma Caki Inducing endoplasmic reticulum stress (ERS) mediates apoptosis. [ 59 , 60 ] Colorectal cancer WS480, HT-29, HCT-116, RKO, SW-480, SW-620, Caco-2 Inducing ERS-mediated autophagy and apoptosis, G2/M arrest.…”
Section: The Anti-tumor Efficacy Of Wa Against Various Cancersmentioning
confidence: 99%